Advancing the structured analysis of regional innovation in China. Integrating new perspectives in a comprehensive approach - Liefner, Ingo; Kroll, Henning (ERDKUNDE, 2019)
Acknowledging the obvious diversity in development trajectories of Chinese regions, this paper seeks to address the prevalent lack of complexity in comparative studies on that country’s regional innovation systems and innovation outcomes. It argues that the prevalent dichotomy between rich yet idiosyncratic case studies and one-dimensional quantitative benchmarking of ’technological capacities’ limits the explanatory and predictive power of existing research. Against this background, it suggests a structuring heuristic that compiles different perspectives of analysis which earlier studies have identified as important. It emphasizes, firstly, that opportunities for innovation in regional settings are not only shaped by the regional technology base, but also triggered by (latent) demand and access to users. Additionally, the actual manifestation of opportunities is contingent on local stakeholder agency and the shared perceptions and cognitive frames (mindsets) that shape it. This paper states, secondly, that these regional characteristics determine the types of innovation produced. To demonstrate this as well as how this approach can indeed provide additional insights, the authors perform structured literature reviews using the proposed multi-perspective framework.